Assessing the conceptual clarity and evidence base of quality criteria/standards developed for evaluating decision aids. (3rd November 2011) - McDonald, Heather; Charles, Cathy; Gafni, Amiram
Abstract Context Promoting patient participation in treatment decision making is of increasing interest to researchers, clinicians and policy makers. Decision aids (DAs) are advocated as one way to help achieve this goal. Despite their proliferation, there has been little agreement on criteria or standards for evaluating these tools. To fill this gap, an international collaboration of researchers and others interested in the development, content and quality of DAs have worked over the past several years to develop a checklist and, based on this checklist, an instrument for determining whether any given DA meets a defined set of quality criteria. Objective/Methods In this paper, we offer a framework for assessing the conceptual clarity and evidence base used to support the development of quality criteria/standards for evaluating DAs. We then apply this framework to assess the conceptual clarity and evidence base underlying the International Patient Decision Aids Standards (IPDAS) checklist criteria for one of the checklist domains: how best to present in DAs probability information to patients on treatment benefits and risks. Conclusion We found that some of the central concepts underlying the presenting probabilities domain were not defined. We also found gaps in the empirical evidence and theoretical support for this domain and criteria within this domain. Finally, we offer suggestions for steps that should be undertaken for further development and refinement of quality standards for DAs in the future.